Fluoxetine treatment supports predictive validity of the three hit model of depression in male PACAP heterozygous mice and underpins the impact of early life adversity on therapeutic efficacy - Gaszner, Tamás; Farkas, József; Kun, Dániel; Ujvári, Balázs; Berta, Gergely; Csernus, Valér; Füredi, Nóra; Kovács, László Ákos; Hashimoto, Hitoshi; Reglődi, Dóra; Kormos, Viktória; Gaszner, Balázs (Frontiers in Endocrinology, 2022)
According to the three hit concept of depression, interaction of genetic predisposition altered epigenetic programming and environmental stress factors contribute to the disease. Earlier we demonstrated the construct and face validity of our three hit concept-based mouse model. In the present work, we aimed to examine the predictive validity of our model, the third willnerian criterion. Fluoxetine treatment was applied in chronic variable mild stress (CVMS)-exposed (environmental hit) CD1 mice carrying one mutated allele of pituitary adenylate cyclase-activating polypeptide gene (genetic hit) that were previously exposed to maternal deprivation (epigenetic hit) vs. controls. Fluoxetine reduced the anxiety level in CVMS-exposed mice in marble burying test, and decreased the depression level in tail suspension test if mice were not deprived maternally. History of maternal deprivation caused fundamental functional-morphological changes in response to CVMS and fluoxetine treatment in the corticotropin-releasing hormone-producing cells of the bed nucleus of the stria terminalis and central amygdala, in tyrosine-hydroxylase content of ventral tegmental area, in urocortin 1-expressing cells of the centrally projecting Edinger-Westphal nucleus, and serotonergic cells of the dorsal raphe nucleus. The epigenetic background of alterations was approved by altered acetylation of histone H3. Our findings further support the validity of both the three hit concept and that of our animal model. Reversal of behavioral and functional-morphological anomalies by fluoxetine treatment supports the predictive validity of the model. This study highlights that early life stress does not only interact with the genetic and environmental factors, but has strong influence also on therapeutic efficacy.